Maternal Overnutrition During Gestation in Sheep Alters Autophagy Associated Pathways in Offspring Heart - Liu, Yang; Ding, Qiyue; Halderson, Steven J.; Arriola Apelo, Sebastian I.; Jones, Amanda K.; Pillai, Sambhu M.; Hoffman, Maria L.; Reed, Sarah; Govoni, Kristen E.; Zinn, Steven A.; Guo, Wei (Frontiers in Genetics, 2022)
Poor maternal nutrition during gestation can negatively affect offspring growth, development, and health pre- and post-natally. Overfeeding during gestation or maternal obesity (MO) results in altered metabolism and imbalanced endocrine hormones in animals and humans which will have long-lasting and detrimental effects on offspring growth and health. In this study, we examined the effects of overnutrition during gestation on autophagy associated pathways in offspring heart muscles at two gestational and one early postnatal time point. Our results revealed significant interactions of maternal diet by developmental stages for offspring autophagy signaling. Overfeeding did not affect the autophagy signaling at mid-gestation day 90 (GD90) in both male and female offspring; however, overfeeding during gestation significantly increased autophagy signaling at a later developmental stage (GD135 and day 1 after birth) in both males and females. We also identified a sexual dimorphic response in which female progeny was more profoundly influenced by maternal diet than male progeny regardless of developmental stages. MO increases the level of cortisol, a regulator of autophagy, in both mother and offspring. Hence, we determined the cortisol concentrations in male and female hearts at three developmental stages. We did not observe any differences between males and females or between overfeeding and control groups. Our results reveal that MO alters autophagy associated pathways in both genders at later developmental stages with more profound effects in females. Altered autophagy protein marks may not be induced by the stress hormone, cortisol.